Soil texture, soil physicochemical properties and climatic data from the PhytOakmeter plot DKr (Kreinitz, Germany) - Sylvie Herrmann; Marie-Lara Bouffaud (PANGAEA, 2025)
PhytOakmeter (www.phytoakmeter.de) is a field platform using the Quercus robur oak clone DF159 outplanted since 2010. This platform is used to monitor the impact of climate change and land use management on the "soil - plant - interactor" complex. Sites from PhytOakmeter are located either in forest or grassland habitats and represent a wide range of environmental contexts with specific stressors. All sites are equipped with loggers measuring air and soil temperature and soil moisture. Soil cores have been collected to analyze their chemical and physical characteristic. The DKr plot in Kreinitz (Germany) started in 2010 with 12 oak trees outplanted yearly between 2010 and 2019 over two 11m x 15m grassland plots. Soil temperature and soil moisture were measured between 2016 and 2025, and soil chemistry was assessed yearly in the root-affected zone of trees aged between one and five years. Soil porosity and texture were evaluated in 2020. The bundled publication is supplemented by recorded precipitation and weather data from an automatic weather station located on site.